Problems and Solutions of Training and Re-Training of Mechanics-Drivers of Combat Vehicles in Military Units and Training Institutions within the Armed Forces JV - Fayzilvakhobovich, Sarimsakov Madaminjon (Research Parks Publishing LLC, 2023)
The training of combat vehicle mechanics-drivers should be aimed at achieving high management skills in various complex conditions, forming will and determination in them, creating a sense of responsibility for the technical adjustment and combat readiness of vehicles.